1986
DOI: 10.1016/s0735-1097(86)80157-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium sulfate on cardiac conduction and refractoriness in humans

Abstract: Magnesium has been used empirically for several decades in the treatment of atrial and ventricular arrhythmias in patients with normal and decreased serum magnesium levels. However, a systematic evaluation of the effects of magnesium on cardiac conduction and refractoriness in humans has not been described. In this study, the electrocardiographic and electrophysiologic effects of magnesium were determined in 10 patients with normal baseline serum magnesium and other electrolyte levels. Six grams of magnesium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
4
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 15 publications
2
58
4
1
Order By: Relevance
“…During hypermagnesemia, both atrial and ventricular pacing thresholds were markedly increased, but these were within normal ranges when a cardiac electrophysiologic study was performed under conditions of normomagnesemia. The results of studies on the electrophysiologic effects of hypermagnesemia are conflicting (13)(14)(15), but to our knowledge, this is the first case report to show that hypermagnesemia can cause an increased cardiac pacing threshold, at least in the severe cases.…”
Section: Discussionmentioning
confidence: 82%
“…During hypermagnesemia, both atrial and ventricular pacing thresholds were markedly increased, but these were within normal ranges when a cardiac electrophysiologic study was performed under conditions of normomagnesemia. The results of studies on the electrophysiologic effects of hypermagnesemia are conflicting (13)(14)(15), but to our knowledge, this is the first case report to show that hypermagnesemia can cause an increased cardiac pacing threshold, at least in the severe cases.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, there is convincing evidence that magnesium infusion is slowing conduction through the atrioventricular node and thus prolongs the PR interval. [42][43][44][45][46] The relation between low serum magnesium and prolongation of the PR interval might be caused by the same mechanism as the relation between low serum magnesium and QTc prolongation: Decreased serum magnesium levels after SAH are followed by increased cytosolic magnesium and consequent prolongation of the PR interval.…”
Section: Pr Intervalmentioning
confidence: 99%
“…19 Mg increases sinus node recovery time, atrioventricular node conduction time, and the atrioventricular node refractory period, and thereby may decrease the ventricular rate during atrial arrhythmias. 20,21 The electrophysiological properties of Mg combined with its excellent safety profile would seem to make Mg a good target for use in facilitating electric cardioversion. Previous studies have shown a benefit of Mg in patients with AF by increasing the success of pharmacological cardioversion and by decreasing the incidence of postoperative AF.…”
Section: Discussionmentioning
confidence: 99%